The Meaning and Purpose of Primary Tooth Disposal Rituals: Implications for Pediatric Dental Professionals - Parsons, Clara L. B.; Mountain, Rebecca V.; Lau, Agnes; Troulis, Maria J.; Bidlack, Felicitas B.; Dunn, Erin C. (Frontiers in Dental Medicine, 2021)
Background: Rituals for disposing of exfoliated primary teeth exist in virtually all cultures around the globe, suggesting an important psychological and social function and milestone of growth for young children and parents. However, the meaning and purpose of these traditions have not yet been thoroughly explored in the dental literature. Aim: The primary aim of this perspective is to discuss the meaning and purpose of primary tooth disposal rituals, and how these rituals impact the practice of dental professionals. Design: Literature addressing the meaning and purpose of tooth disposal rituals was reviewed using electronic databases (PubMed, Google Scholar). This literature is interpreted in the context of its importance to the field of pediatric dentistry. Results: Primary tooth disposal rituals are likely practiced as a rite-of-passage to ease the transition from early to later childhood, to counteract anxiety, trauma, or pain experienced by children of tooth-shedding age, and to honor spiritual or religious beliefs that are thought to protect children and aid their healthy development. Conclusions: By understanding the significance and diversity of these traditions, dental professionals can: potentially increase their cultural competence to engage with increasingly diverse pediatric patient populations, improve their ability to prevent dental anxiety, and ensure more timely primary oral care.